Dinamika dan Perubahan Sosial (Kasus Orang Melayu di Sumatera Timur) - Usman Pelly (Antropologi Indonesia, 1991)
Both ecological and population changes are important factors to encourage social and cultural changes in a society. Such changes might not be absorbed and accepted if it against community cultural values and it might raises and inner obsession. Hence, it leads missing cultural ethos and identity in society. This article elaborates those problems - from historical perspective - with a case of Malay people In East Sumatera. The ecological and population changes have happened since 19th century when Dutch founded wide plantations. With coming of various ethnic groups to East Sumatera, it insisted Malays to be minority in terms of occupation, political government, business and number of population especially in urban areas. It occurred necession and indifferent attitude (apathy) of Malay towards the fast changes.